Modeling integrated soil fertility management for maize production in Kenya using a Bayesian calibration of the DayCent model - Laub, M.; Necpalova, M.; Van de Broek, M.; Corbeels, M.; Ndungu, S.M.; Mucheru-Muna, M.W.; Mugendi, D.; Yegon, R.; Waswa, W.; Vanlauwe, B.; Six, J. (Copernicus GmbH, 2024)
Sustainable intensification schemes such as integrated soil fertility management (ISFM) are a proposed strategy to close yield gaps, increase soil fertility, and achieve food security in sub-Saharan Africa. Biogeochemical models such as DayCent can assess their potential at larger scales, but these models need to be calibrated to new environments and rigorously tested for accuracy. Here, we present a Bayesian calibration of DayCent, using data from four long-term field experiments in Kenya in a leave-one-site-out cross-validation approach. The experimental treatments consisted of the addition of low- to high-quality organic resources, with and without mineral nitrogen fertilizer. We assessed the potential of DayCent to accurately simulate the key elements of sustainable intensification, including (1) yield, (2) the changes in soil organic carbon (SOC), and (3) the greenhouse gas (GHG) balance of CO2 and N2O combined.